Designing Organizational Culture Through the Z Theory Modification in the Environment of CV. Indobenua Global Mandiri, Sidoarjo - Tiffany Esperances Deandra; I Gede Arimbawa; Elok Damayanti (IJEBD (International Journal of Entrepreneurship and Business Development), 2019)
Purpose: This study aims to designing organizational culture through the Z Theory modification in the environment of CV. Indobenua Global Mandiri, Sidoarjo. Design/methodology/approach: This study used a qualitative research approach and post positivism philosophy method, Findings: The results of organizational culture design in CV. Indobenua Global Mandiri Sidoarjo formed through modification of the value system derived from Z theory, such as: implicit control mechanism and the prevailing culture in the CV. Indobenua Global Mandiri, Research limitations/implications: CV. Indobenua Global Mandiri, Sidoarjo. Practical implications: harmonizing relationships among employees, and responsibilities according to job description, and control mechanisms by superiors directly. Originality/value: Paper type: This paper can be categorized as case study paper.